A transformation gap? : American innovations and European military change - Terriff, Terry, 1953-; Osinga, Frans P. B.; Farrell, Theo, 1967- (Stanford University Press, 2010)
This study assesses the extent and trajectory of military transformation across a range of European NATO member states, setting their transformation progress against that of the US, and examining the complex mix of factors driving military transformation in each country. It reveals not only the nature and extent of the transatlantic gap, but also identifies an enormous variation in the extent and pace of transformation among the European allies, suggesting both technological and operational gaps within Europe.